Effects of accentuated eccentric loading on muscle properties, strength, power, and speed in resistance-trained rugby players - Douglas, J.; Pearson, S.; Ross, A.; McGuigan, M. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to determine the effects of slow and fast tempo resistance training incorporating accentuated eccentric loading (AEL) compared with traditional resistance training (TRT) in trained rugby players. Fourteen subjects (19.4 ± 0.8 years, 1.82 ± 0.05 m, 97.0 ± 11.6 kg, and relative back squat 1 repetition maximum [1RM]: 1.71 ± 0.24 kg/BM) completed either AEL (n = 7) or TRT (n = 7) strength and power protocols. Two 4-week phases of training were completed. The first phase emphasized a slow eccentric tempo, and the second phase emphasized a fast eccentric tempo. Back squat 1RM, inertial load peak power, drop jump reactive strength index (RSI), 40-m speed, maximum sprinting velocity (Vmax), and vastus lateralis (VL) muscle architectural variables were determined at baseline and after each phase of training. Slow AEL elicited superior improvements in back squat 1RM (+0.12 kg/BM; effect size [ES]: 0.48; and 90% confidence interval [CI]: 0.14, 0.82), 40-m time (-0.07 seconds; ES: 0.28; and CI: 0.01-0.55), and Vmax (+0.20 m/s; ES: 0.52; and CI: 0.18-0.86) vs. slow TRT. Fast AEL elicited a small increase in RSI but impaired speed. There was a likely greater increase in peak power with fast TRT (+0.72 W/kg; ES: 0.40; and CI: 0.00-0.79) vs. fast AEL alongside a small increase in VL pennation angle. The short-term incorporation of slow AEL was superior to TRT in improving strength and maximum velocity sprinting speed in rugby players undertaking a concurrent preparatory program. The second 4-week phase of fast AEL may have exceeded recovery capabilities compared with fast TRT.